The politics of vigilance in southeastern Nigeria - Pratten, D (Wiley-Blackwell on behalf of the Institute of Social Studies, 2006)
This article argues that governance can be best analysed within modes of vigilance. Where recent work on the post‐colonial state has emphasized the symbolic and practical constitution of the state through surveillance and spatialization, so in counterpoint, this analysis illustrates that social engagement with the state is based on conceptions of vigilance and practices of counter‐surveillance with both spatial and temporal dimensions. Drawing on an ethnography of Annang youth associations in southeastern Nigeria, this analysis outlines how the micro‐politics of vigilance are based on knowledge of the states' patrimonial ‘ways of operating’ and processes which define internal, localized rights, registers and styles of action. This argument is based on an analysis of popular responses to disorder which contribute to an ‘insurgent’ construction of the public realm in which groups marginalized and excluded challenge the logic, locations, patterns of discourse and constructions of the public good.